Survey of organ‐derived small extracellular vesicles and particles (sEVPs) to identify selective protein markers in mouse serum - Kotb Abdelmohsen; Allison B. Herman; Angelica E. Carr; Charnae’ A. Henry‐Smith; Martina Rossi; Qiong Meng; Jen‐Hao Yang; Dimitrios Tsitsipatis; Alhassan Bangura; Rachel Munk; Jennifer L. Martindale; Carlos J. Nogueras‐Ortiz; et al. (Journal of Extracellular Biology, 2023)
Abstract Extracellular vesicles and particles (EVPs) are secreted by organs across the body into different circulatory systems, including the bloodstream, and reflect pathophysiologic conditions of the organ. However, the heterogeneity of EVPs in the blood makes it challenging to determine their organ of origin. We hypothesized that small (s)EVPs (<100 nm in diameter) in the bloodstream carry distinctive protein signatures associated with each originating organ, and we investigated this possibility by studying the proteomes of sEVPs produced by six major organs (brain, liver, lung, heart, kidney, and fat). We found that each organ contained distinctive sEVP proteins: 68 proteins were preferentially found in brain sEVPs, 194 in liver, 39 in lung, 15 in heart, 29 in kidney, and 33 in fat. Furthermore, we isolated sEVPs from blood and validated the presence of sEVP proteins associated with the brain (DPP6, SYT1, DNM1L), liver (FABPL, ARG1, ASGR1/2), lung (SFPTA), heart (CPT1B), kidney (SLC31), and fat (GDN). We further discovered altered levels of these proteins in serum sEVPs obtained from old mice compared to young mice. In sum, we have cataloged sEVP proteins that can serve as potential biomarkers for organ identification in serum and show differential expression with age.